ERITRODERMA AKIBAT REAKSI OBAT ALLOPURINOL - Emeralda, Pradissa Avia; Savitri, Dwiana (Universitas Pahlawan, 2024)
Erythroderma is a condition of generalized erythema and scaling of the skin. More than 90% of the body surface area are involved in this condition accompanied by a various degree of scaling. This is potentially life-threatening and has been associated with DRESS syndrome. 1,3 The aim of this case report is to discuss the allopurinol drug reaction as aetiology of erythroderma, its clinical manifestations and management of therapy. We report a case of a 55-year-old female patient who had a generalized erythema, pruritus, malaise and edema of her face since 7 days before admitted. She had history diabetes mellitus type 2, and was in oral allopurinol treatment for last 2 weeks. Extensive generalized erythematous plaques and hyperkeratotic scales were observed in the face, neck, chest, arms, legs, back, and gluteal. Laboratory workup revealed peripheral blood eosinophilia, mild hypoalbuminemia, hyperglycemia, and elevated liver enzyme level. She was hospitalized and got treatment with dermatologist and internist. Erythroderma is an emergency case in dermatovenereology and in severe case it needs therapy and hospitalization to avoid complication. Management of erythroderma include discontinuing of any potential causative drug, maintaining skin moisture and integrity, adequate hydration and nutrition, maintaining electrolyte balance, and antibiotics for secondary infection. Patient with drug-induced erythroderma with internal organ involvement has been associated with DRESS syndrome and needs further observation in cardiac, liver, and kidney status. Allopurinol is potential drug which can trigger erythroderma. Erythroderma is a life-threatening disease especially in severe case. It is important to increase awareness in allopurinol medication and need a careful assessment and treatment to avoid complication.